2020
DOI: 10.21203/rs.3.rs-104040/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous use of glycomacropeptide in the nutritional management of patients with phenylketonuria: a clinical perspective

Abstract: Background: In phenylketonuria (PKU), modified casein glycomacropeptide supplements (CGMP-AA) are used as an alternative to the traditional phenylalanine (Phe)-free L-amino acid supplements (L-AA). However, studies focusing on the long-term nutritional status of CGMP-AA are lacking. This retrospective study evaluated the long-term impact of CGMP-AA over a mean of 29 months in 11 patients with a mean age at CGMP-AA onset of 28 years (range 15 to 43) [8 females; 2 hyperphenylalaninaemia (HPA), 3 mild PKU, 3 clas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Based on the included studies, children and adolescents who were given CGMP-AA, a mixture of CGMP and essential and conditional amino acids, had significantly higher levels of plasma phenylalanine in comparison to those given a phenylalanine-free formula. However, these findings differ from a meta-analysis (61) and few clinical trials which only found a negligible difference in phenylalanine concentrations between the two groups (58,62,63). Participant age could explain the disparity of the findings as the only participants included in this scoping review were children and adolescents while the other studies included adults.…”
Section: Discussioncontrasting
confidence: 77%
“…Based on the included studies, children and adolescents who were given CGMP-AA, a mixture of CGMP and essential and conditional amino acids, had significantly higher levels of plasma phenylalanine in comparison to those given a phenylalanine-free formula. However, these findings differ from a meta-analysis (61) and few clinical trials which only found a negligible difference in phenylalanine concentrations between the two groups (58,62,63). Participant age could explain the disparity of the findings as the only participants included in this scoping review were children and adolescents while the other studies included adults.…”
Section: Discussioncontrasting
confidence: 77%
“…Whilst not significant, Daly et al (2021) demonstrated improved LBM in people with PKU taking a cGMP-based protein substitute. No differences in body composition parameters were reported in adolescents and adults taking L-AA compared to cGMP [45,46].…”
Section: Type Of Protein Substitutementioning
confidence: 84%
“…Thirty-seven studies, including 24 full text papers and 13 conference abstracts, reported anthropometric assessments of protein status. Seven were interventional studies but only three reported the study design; two had a retrospective design [45,46] and one was…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations